2003
DOI: 10.5650/jos.52.205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phytosterol Ester-Enriched Vegetable Oil on Serum Cholesterol and Assessment of Safety in Healthy Men.

Abstract: Abstract:The purpose of this study was to determine the effects of phytosterol esterenriched vegetable oil on the serum concentration of cholesterol and to assess its safety in healthy subjects with normocholesterolemics. Twenty-two healthy subjects completed this study in a double blind, parallel arm design. The subjects were randomly divided into 2 groups: control group (n = 11) and phytosterol ester-enriched group (n = 11), and fed either 42 g of phytosterol ester-enriched vegetable oil or control vegetable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…Our study is the first study that had repeated measurements of plasma PS within a 12 weeks timeframe after a daily intake of 3 g PS, which is the maximal intake recommendation. We observed that plasma sitosterol and campesterol concentrations were similar after 4 weeks and after 8 and 12 weeks of intervention, confirming previously reported data for low doses of PS (<0.5 g/d) [20,21]. Longer-term intervention studies (up to 85 weeks) have also shown that plasma PS do not further increase with sustained PS intake [22,23].…”
Section: Discussionsupporting
confidence: 90%
“…Our study is the first study that had repeated measurements of plasma PS within a 12 weeks timeframe after a daily intake of 3 g PS, which is the maximal intake recommendation. We observed that plasma sitosterol and campesterol concentrations were similar after 4 weeks and after 8 and 12 weeks of intervention, confirming previously reported data for low doses of PS (<0.5 g/d) [20,21]. Longer-term intervention studies (up to 85 weeks) have also shown that plasma PS do not further increase with sustained PS intake [22,23].…”
Section: Discussionsupporting
confidence: 90%
“…In the four remaining studies (Matvienko et al, 2002;Deveraj et al, 2004;Saito et al, 2006;Seki et al, 2003b) it took longer than two weeks before the maximum reduction was reached.…”
Section: Minimum Duration For Effect Of Plant Sterols/stanolsmentioning
confidence: 98%
“…In seven (Blair et al, 2000;Gonzales et al, 2007;Homma et al, 2003, treatment arms 1 and 2; Maki et al, 2001, treatment arm 1;Niittynen et al, 2007;Nguyen et al, 1999, treatment arm 1) out of 17 treatment arms in which the earliest LDL-cholesterol measurement was made after two weeks of the intervention, the maximum LDL-cholesterol lowering effect was already attained after 2 weeks of the intervention; in another six (Hallikainen and Uusitupa, 1999, treatment arms 1 and 2; Maki et al, 2001, treatment arm 2;Nguyen et al, 1999, treatment arms 2 and 3;Seki et al, 2003a) of these 17 treatment arms most of the reduction was already achieved after two weeks. In the four remaining studies (Matvienko et al, 2002;Deveraj et al, 2004;Saito et al, 2006;Seki et al, 2003b) it took longer than two weeks before the maximum reduction was reached.…”
Section: Minimum Duration For Effect Of Plant Sterols/stanolsmentioning
confidence: 98%
“…Lipid changes in Amazon reviews were compared with lipid changes reported in a systematic review (Wu et al, 2009). I extracted the average baseline lipid level and the average followup lipid level from each relevant study arm (Devaraj et al, 2006(Devaraj et al, , 2004Doornbos et al, 2006;Goldberg et al, 2006;Jauhiainen et al, 2006;Korpela et al, 2006;Maki et al, 2001;Matvienko et al, 2002;Mensink et al, 2002;Miettinen et al, 1995;Polagruto et al, 2006;Quílez et al, 2003;Seki et al, 2003;Woodgate et al, 2006). Four of the 20 studies reported in Wu et al (2009) were excluded: in two cases the original study report was unavailable and in two cases the intervention involved substantial dietary changes, over and above stanols/sterols (Hallikainen and Uusitupa, 1999;Jones et al, 1999).…”
Section: Data Collectionmentioning
confidence: 99%